2020
DOI: 10.11591/eei.v9i2.2073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of positive emotion in children mobile learning application

Abstract: This paper presents the evaluation of positive emotion in children's mobile learning applications. The mobile learning application is a teaching aid that can help students to self-study and increase the students’ interest in learning especially children. This paper will discuss how mobile learning application affects the children interest in school. The evaluation method implemented to evaluate the rate of positive emotion elicited by the children using mobile learning applications was a mixed method of qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Several factors are taken into consideration in generating the EEG dataset for emotion recognition, including [11]: a) Stimulus media: The literature studies showed several categories of stimuli to evoke emotions such as audio [16], [17], visual, and audio-visual media [14] as well as others including the ambient assisted living (AAL) technology [18], a combination of music, video, and game stimuli [19], mobile learning application [20], augmented reality (AR) [21], virtual reality (VR) [22], [23], and tactile enhanced multimedia (TEM) [24]. b) Proper stimuli presentation setup [11].…”
Section: Rq 1: What Factors Need To Be Considered To Generate and Distribute Eeg Data To Represent Emotional Reactions?mentioning
confidence: 99%
“…Several factors are taken into consideration in generating the EEG dataset for emotion recognition, including [11]: a) Stimulus media: The literature studies showed several categories of stimuli to evoke emotions such as audio [16], [17], visual, and audio-visual media [14] as well as others including the ambient assisted living (AAL) technology [18], a combination of music, video, and game stimuli [19], mobile learning application [20], augmented reality (AR) [21], virtual reality (VR) [22], [23], and tactile enhanced multimedia (TEM) [24]. b) Proper stimuli presentation setup [11].…”
Section: Rq 1: What Factors Need To Be Considered To Generate and Distribute Eeg Data To Represent Emotional Reactions?mentioning
confidence: 99%
“…Some physics learning topics that are difficult for students to imagine can be made an interactive application or platform, from research by Mardiana & Kuswanto, (2017);Criollo-C et al, (2021); Tan & Heh., (2019);Ruiz-Rube et al, (2019) with the development of interactive applications for mobile learning, can improve critical thinking and problem solving skills, and students show positive responses, more active, high level of satisfaction. Interactive media can trigger positive mental health and increase students' selfconfidence (Gharaibeh & Gharaibeh, 2020;Gasah et al, 2020).…”
Section: Literature Review Of Mobile Web and E-learning For Physics L...mentioning
confidence: 99%
“…A deep network for accurate emotion recognition and a network for binary classification of emotions as positive or negative (He & Zhang, 2018). Since emotion can be either positive or negative, it was vital to choose the appropriate strategy or point of view to show that a positive emotion was truly produced (Gasah et al, 2020). Emotion differentiation, or the ability to experience and recognize emotions in detail, has been linked to wellbeing.…”
Section: Fig 1 -The Differences In Response Average Between Male and ...mentioning
confidence: 99%